BIM and Parametric Design in Academia and Practice: The Changing Context of Knowledge Acquisition and Application in the Digital Age. (March 2015) - Holzer, Dominik
This paper explores the consequences of the use of Building Information Modeling (BIM) and Parametric Design on contemporary architectural practice and associated changes to the roles and responsibilities therein. Knowledge changes associated to new skill-sets of young graduates and their positioning among experienced professionals will be analysed. On one hand the paper will scrutinise how the use of BIM and Parametric design challenges design and delivery of projects, on the other hand the paper will reflect on the extent academic institutions can or should respond to the challenges. What are the opportunities inherent to these changes in practice? How should they influence current academic curricula that include computational design and digital architecture? Based on targeted interviews with recent graduates who entered practice, a number of responses to the challenges and opportunities will be presented by the author for further consideration.